2014
DOI: 10.1021/jf504648f
|View full text |Cite
|
Sign up to set email alerts
|

PUFA Biosynthesis Pathway in Marine Scallop Chlamys nobilis Reeve

Abstract: Long-chain polyunsaturated fatty acids (LC-PUFAs) are essential in important physiological processes. However, the endogenous PUFA biosynthesis pathway is poorly understood in marine bivalves. Previously, a fatty acyl desaturase (Fad) with Δ5 activity was functionally characterized and an elongase termed Elovl2/5 was reported to efficiently elongate 18:2n-6 and 18:3n-3 to 20:2n-6 and 20:3n-3 respectively in Chlamys nobilis. In this study, another elongase and another Fad were identified. Functional characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 36 publications
(74 reference statements)
3
33
1
Order By: Relevance
“…The result is consistent to the previous study in the mollusks [4,27] and in the vertebrates [24,28].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The result is consistent to the previous study in the mollusks [4,27] and in the vertebrates [24,28].…”
Section: Discussionsupporting
confidence: 93%
“…Instead bivalves have been thought to obtain the PUFAs from their diets [30,31]. However, in the present study, the oyster was identified to have the ability to biosynthesize PUFAs by itself, and previous study in two mollusks of O. vulgaris [4] and C. nobilis [16] had the same findings, respectively. Therefore, we conclude that marine mollusks have the ability to biosynthesize PUFAs by themselves.…”
Section: Discussionsupporting
confidence: 39%
See 3 more Smart Citations